O estudo do limite de transporte interfilamentar de supercorrentes em amostras supercondutoras de BSCCO - Deimling, Cesar Vanderlei (2006)
In this work, we have studied the behavior of the line H*(T) in filamentary samples of BSCCO, which were grown by the LFZ technique, Laser Floating Zone. Previously studied in other specimens prepared by specific routes for exemple, samples of Mgdeficient MgB2; YBCO prepared by the Sol-Gel technique; or polycrystalline samples of Nb the H*(T) frontier defines the region in the magnetic fase diagram above which the intergranular critical current density vanishes. The H*(T) line is an extrinsic feature, dependent on the preparation and subsequent heat treatment of the samples, observed only in specimens having a narrow intergranular critical current distribution, which can be obtained controlling properties such as granularity. Measurements of ac-susceptibility as a function of temperature has been performed, for different values of the magnetic excitation field, from which a point was determined, T*, above which the ac-susceptibility is independent of the intensity of the magnetic excitation field. This means that, above T*, only the intrafilamentary regions are able to transport supercurrents. Relating the magnetic measurements with results of transport measurements four terminals and flux transformer we have found a complete similarity between T* and the offset critical temperature, Tc off. We have also verified that T* depends on the field H, so that the magnetic phase diagram includes an extrinsic frontier H*(T), confirming the original expectation that the intergranular space surrounding the grains of a system with controlled granularity, may constitute an efficient set of pinning centers for magnetic flux, what occurs, in fact, in the region to which H*(T) is an upper bound, where the intergranular critical currents are nonzero. It is quite impressive that different samples present practically coincident H*(T) frontiers, what reinforces the prediction that the studied line has a universal character, as long as the sample fulfills the criterion of exhibiting a narrow intergranular critical current distribution.